Repetitive transcranial magnetic stimulation promotes functional recovery and differentiation of human neural stem cells in rats after ischemic stroke - Peng, Jiao-Jiao; Sha, Rong; Li, Ming-Xing; Chen, Lu-Ting; Han, Xiao-Hua; Guo, Feng; Chen, Hong; Huang, Xiao-Lin (Experimental neurology, 2019)
Stem cells hold great promise as a regenerative therapy for ischemic stroke by improving functional outcomes in animal models. However, there are some limitations regarding the cell transplantation, including low rate of survival and differentiation. Repetitive transcranial magnetic stimulation (rTMS) has been widely used in clinical trials as post-stroke rehabilitation in ischemic stroke and has shown to alleviate functional deficits following stroke. The present study was designed to evaluate the therapeutic effects and mechanisms of combined human neural stem cells (hNSCs) with rTMS in a middle cerebral artery occlusion (MCAO) rat model. The results showed that human embryonic stem cells (hESCs) were successfully differentiated into forebrain hNSCs for transplantation and hNSCs transplantation combined with rTMS could accelerate the functional recovery after ischemic stroke in rats. Furthermore, this combination not only significantly enhanced neurogenesis and the protein levels of brain-derived neurotrophic factor (BDNF), but also rTMS promoted the neural differentiation of hNSCs. Our findings are presented for the first time to evaluate therapeutic benefits of combined hNSCs and rTMS for functional recovery after ischemic stroke, and indicated that the combination of hNSCs with rTMS might be a potential novel therapeutic target for the treatment of stroke. •hNSCs are successfully differentiated from hESCs for transplantation in vitro.•Combination treatment of ischemic stroke with hNSCs and rTMS accelerates functional recovery.•hNSCs + rTMS increases endogenous neurogenesis in the SVZ and activates BDNF-TrkB signaling pathway.•rTMS promotes the differentiation of hNSCs after transplantation in MCAO rats.